(untitled) (Global Journal of Science Frontier Research, 2023)
Plant breeding programs have been investing in the development of high commercial standard onions; thus, they depend on the genetic resources available for obtaining commercial hybrids. The objective of this study was to evaluate genetic parameters and diversity, and phenotypic and genotypic correlations of characters related to onion production. The experiment was conducted in Uberlândia, Minas Gerais, Brazil. Fifty-three onion strains were evaluated, and a randomized block design was used. The number of plant and bulb characteristics evaluated was 13. The statistical analyses were performed using Genes and R software. A genetic variability among the genotypes was found for most of the characters at 1% level of significance in the F test. The heritability of most characters presented moderate to high values (≥ 70%) and high CVg/CVe ratio (≥ 1). The UPGMA method separated the genotypes into 20 groups, while the Tocher method separated them into 19 groups. The groups that stood out were V, XIV, XV, XV, XVI, XVII, XVIII, XIX, and XX. The results of t-test showed six significant phenotypic correlations with low to moderate degree of association, and the genotypic correlations, in most cases, were higher than the phenotypic ones and showed the same sign. From the genetic parameters studied, the possibility of gains in the selection is high. The separation of groups of divergent genitors was possible due to the wide genetic variability for the studied characters. Moreover, the phenotypic and genotypic correlations showed that indirect selection is not feasible.